Discourse Analysis of PM Imran Khan’s Speeches during Foreign Visits for Economic Recovery of Pakistan - Muhammad Tahsin (Linguistics and Literature Review, 2019)
Discourse analysis is associated with the comprehension process of discursive construction and its social outcomes. The aim of this research is to investigate the discursive practices in the form of linguistic devices employed by PM Imran Khan to construct the discourse of economic recovery for Pakistan. A qualitative content analysis of data (collected from a sample of three speeches during his official visits to Saudi Arabia, China and Turkey) was conducted to address the underlying research questions. Frequency of recurring words was also measured to find the variation in their use. The findings unveil that a discourse of hope regarding economic recovery of Pakistan, was constructed by the Prime Minister successfully manipulating a variety of discursive practices including the use of specific terminology, repetition, constructive self-impression, figurative expressions, active voice, cohesiveness and allusions for attracting the foreign investors and giving a ray of hope to the Pakistanis back home.